Property estimate for inkjet based direct digital manufacturing. Issue 2 (4th March 2018) - Yu, K. M.; Tang, Y. M.; Chan, L. C.
ABSTRACT: Nowadays, additive manufacturing (AM) is an emerging manufacturing technology growing rapidly. Superior to the traditional manufacturing, AM can produce unique objects quickly and at a low cost. However, most of the AM technology can only product object with single or a few color and material. Inkjet based direct digital manufacturing (DDM) can fabricate objects with different colors and materials. However, characterization of objects materials fabricated by DDM still has great complexity. Therefore, we propose to estimate the property of the inkjet material fabricated by the DDM in a reasonable range by interpolating the materials with the arithmetic and harmonic limit. By comparing the material property of the digital material obtained from a literature with our proposed models, the material property of the digital material fits into the range of our calculated arithmetic sum and harmonic sum. GRAPHICAL ABSTRACT: